Understanding formulaic language a second language acquisition perspective - Siyanova-Chanturia, Anna; Pellicer-Sanchez, Ana (Routledge, 2019)
"Multi- and interdisciplinary in nature, Understanding Formulaic Language brings together leading researchers in the field to provide a state-of-the-art account of what is known about the acquisition, processing, and use of formulaic language, focusing, in particular, on the recent developments and directions for future research. Three distinct but complementary perspectives on the study of formulaic language are presented - the cognitive and psycholinguistic, socio-cultural and pragmatic, and pedagogical - attesting to a rich research base. Understanding Formulaic Language: A Second Language Acquisition Perspective is an essential resource for established researchers and graduate students in second language acquisition and pedagogy, corpus and cognitive linguistics, psycholinguistics, sociolinguistics, and pragmatics"--
Description based on print version record
Keywords: Second language acquisition; Linguistic analysis (Linguistics); Linguistic models